Two new synonymies in the genus Lispe (Diptera: Muscidae) - Ge, Ying-Qiang; Gao, Yun-Yun; Zhang, Dong (Zootaxa, 2018)
Two new junior synonymies in Lispe are proposed herein: L. bivittata Stein, 1909 = L. guizhouensis Wei, 2006 syn. nov. and L. nicobarensis Schiner, 1868 = L. leigongshana Wei & Yang, 2007 syn. nov. Both species are diagnosed with photographs and terminalia illustrations. The identity of L. subbivittata Mou, 1992, a former subspecies of L. bivittata, is discussed.